Sociodemographic Questionnaire Modules for Comparative Social Surveys - Hoffmeyer-Zlotnik, Jürgen H.P (SpringerBriefs in Population Studies,, 2018)
Above all, this book focuses on the application of sociodemographic survey questions. Based on theoretical foundations, it addresses the operationalization of variables and presents socio-demographic questionnaire modules for within- and across-country comparative survey research. The book pursues three main objectives: to provide a thorough and comprehensive overview of the survey instruments currently available for the measurement of sociodemographic variables in cross-national comparative research; to offer the reader a set of harmonized international demographic standards; and to show how these standards can be implemented by the various parties involved in international comparative surveys - from the central project coordinators, to the researchers on the national survey teams, to the fieldwork agencies and their interviewers, to respondents, and eventually, to the data processing experts preparing the datasets for comparative analysis. The book offers a valuable resource for researchers, practitioners and students actively involved in producing and analyzing sociodemographic survey data. The typical readers will be social science researchers, qualified consultants and professionals interested in the field of (comparative) survey research. The book can also serve as a useful supplement to introductory textbooks on survey methodology and is suitable for Bachelor and Master students of the social sciences. .